Frequency Division using a Soliton-Injected Semiconductor Gain-Switched Frequency Comb - Weng, Wenle; Kaszubowska-Anandarajah, Aleksandra; Liu, Junqiu; Anandarajah, Prince M.; Kippenberg, Tobias J. (2020 Conference on Lasers and Electro-Optics (CLEO), 2020)
By injecting a soliton microcomb into a semiconductor laser that is driven by a sinusoidal current at the subharmonic frequencies of the soliton rate, we demonstrate broadband gain-switched frequency comb generation and low-noise microwave synthesis.